Communication Ethnography in the Royal Funeral Ritual in the Marapu Community, East Sumba - Wungubelen, Maria Mersi A.; Murtiningsih, Bertha Sri Eko; Susilo, Daniel (UPT Publikasi Ilmiah UNISBA, 2024)
The funeral ritual, also known as 'pa hengingu', is one of the traditional customs of Sumba that have endured to the present day. This research examines the communication events occurring within the Marapu funeral ritual. This study aims to understand the perspectives and values held by the Marapu community by employing a qualitative approach and communication ethnography methodology. This study focuses on traditional communication in the Marapu’s funeral ritual by examining communication activities, such as communication situations, communication events, and communication actions. This study also tries to understand how a cultural group creates meaning, values, and communication practices through cultural events. Research data was collected through observations and interviews with one primary informant and three additional informants. The primary informant was the Funeral Ritual Guide, while the other three informants included the Chief of the Marapu Community, a male community member, and a female community member. The implications of this research for the Marapu community lie in the realm of documentation and archival record benefits. The research findings reveal that the Marapu community highly values kinship and community cooperation—the funeral ritual results from community cooperation involving not only grieving families but all tribal groups within the Marapu community.